2017
DOI: 10.2147/rru.s129490
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic cystitis with recurrent urinary retention: case report

Abstract: Eosinophilic cystitis is a rare inflammatory disease of the bladder whose origin, pathogenesis, and treatment are unknown. Frequency, dysuria, and hematuria are frequent symptoms. Here, we report a rare occurrence of recurrent urinary retention and repetitive catheterization. A 67-year-old male presented with acute urinary retention and intermittent gross hematuria of 2 weeks duration. Urethral catheterization followed by a trial without catheter, was successful. Complete blood count showed presence of eosinop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
(13 reference statements)
0
5
0
1
Order By: Relevance
“…During hospitalization, the eosinophils were found to be decreased in a routine blood test and the patient's symptoms gradually improved. It has previously been suggested that EC may also present a self-healing trend ( 3 ). In the present study, patient 1 presented with similar symptoms 3 years earlier; an ultrasonography revealed thickening of the bladder wall and following 3 days of anti-inflammatory treatment, the symptoms disappeared.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During hospitalization, the eosinophils were found to be decreased in a routine blood test and the patient's symptoms gradually improved. It has previously been suggested that EC may also present a self-healing trend ( 3 ). In the present study, patient 1 presented with similar symptoms 3 years earlier; an ultrasonography revealed thickening of the bladder wall and following 3 days of anti-inflammatory treatment, the symptoms disappeared.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patient 1 was allergen-positive. The authors hypothesize that the onset of the disease in case 1 was associated with allergens and that, with the elimination of inflammatory mediators, symptoms may disappear ( 3 ). It has previously been reported that urine cultures are positive in EC patients ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sur le plan clinique, La symptomatologie de la CE est polymorphe et non spécifique. Les symptômes les plus fréquents étaient la pollakiurie (67%), la dysurie (62%), l'hématurie macroscopique ou microscopique (68%), la douleur sus-pubienne (49%) et la rétention aiguë d'urine (10%) [6, 9]. Chez les enfants, la CE peut se manifester par une énurésie secondaire [10].…”
Section: Discussionunclassified
“…Eosinophilic cystitis (EC) is a rare inflammatory disorder of the bladder whose etiology, pathogenesis, and treatment are unknown. The reported frequent symptoms of this disease include frequency, dysuria, and hematuria [ 1 ]. Although the etiology of EC is unclear, allergies or injuries of the bladder wall appear to be present in most patients [ 2 ].…”
Section: Introductionmentioning
confidence: 99%